Pengaruh Ekstrak Etanol Tumbuhan Anting-anting (Acalypha indica L.) Terhadap Kebuntingan dan Fetus Mencit (Mus musculus) - Kartini Eriani; Wiladatika Wiladatika; Razi Suangkupon (Jurnal Bioleuser, 2017)
The whole plant Acalypha indica L. has been used as a traditional herbal medicine for generations by the society. However, the benefits of the whole plant Acalypha indica L. as a herbal medicine have not been known much, especially as an antifertility plant. It is assumed that the compunds contained within the ethanol extract of the whole plant Acalypha indica L. woulf affect upon one’s reproduction.  This research aimed to know the effect of the ethanol extract the whole plant Acalypha indica L. on pregnancy and fetal with obeserved on prenatal fetal (Mus musculus). It was carried out in july 2011 - february 2012 at Microtechnique Laboratory of  FMIPA Unsyiah. Completely randomized design was applied of the research, consisted of 4 treatments and 5 repetition of each treatment. The treatments were P0 (0 mg/ kg BW (control)), P1 (300 mg/ kg BW), P2 (600 mg/ kg BW), and P3 (900 mg/ kg BW) the ethanol extract of the whole plant  Acalypha indica L. that was given once a day for 7 days. The parameters were number of pregnancy, the average of fetal bodyweight, the number of fetal in uterine, and macroscopic defect. The data was analyzed by analysis of variance and chi-square, also continued by Tukey test. The result showed significant difference of number of pregnancy, the average of fetal bodyweight, and the number of fetal in uterine. The ethanol extract of the whole plant Acalypha indica L. extract could decrease the number of  pregnancy, the average of fetal bodyweight, the number of fetal in uterine on P1 (600 mg/ kg BW) and P2 (900 mg/ kg BW), also could not caused macroscopic defect on fetal.